Pengaruh Pengembangan Media Booklet CPSS Terhadap Kemampuan Kader Kesehatan Dalam Deteksi Dini Stroke - Cecilya Kustanti; Linda Widyarani (STIKes MERCUBAKTIJAYA, 2022)
Stroke has become the leading cause of death in almost all hospitals in Indonesia, which is around 21,1%, was higher than heart and blood vessel diseases (12,9%), TBC (6,7%) and hypertension (5,3%). Stroke prevention and control strategies has played an important role to prevent and reduce disease, disability and death from stroke. One of the strategy can be applied by early detection attack stroke in the community. The purpose of this study is to determine the effect of booklet CPSS as a learning media in health cadres ability In early detection prehospital attack a stroke. This study used a quasi-experimental method with one group pre-post test design, with a purposive sampling technique. The intervention used booklet CPSS. In this study, the average pretest value of knowledge was 59,37±3,102 and the posttest value of knowledge was 84,70±1,236, with a p-value of 0.000, which means that there is a significant difference between the knowledge before and after the intervention.